Antimicrobial Activity of Phytic Acid, Citric Acid, and EDTA with and without Propolis against Enterococcus Faecalis and Candida Albicans - Merve Yeniçeri Özata; Ömer Acer; Özlem Demirci; Mehmet Çolak; Gizem Akın Tartuk (Mashhad University of Medical Sciences, 2022)
Introduction: This study aimed to investigate the antimicrobial efficacy of chelation agents on Enterococcus faecalis (E. faecalis) and Candida albicans (C. albicans) when used alone or in combination with propolis. Methods: One hundred fifty mandibular premolar teeth were selected. Each canal was prepared with Reciproc R25. The roots were then divided into two parts along their long axis (n=300). For E. faecalis and C. albicans, the samples were divided into 16 groups (14 experimental and 2 control) as follows: Group 1A-1B [17% Ethylenediaminetetraacetic acid (EDTA)], Group 2A-2B [10% Citric Acid (CA)], Group 3A-3B [1% phytic acid/inositol hexaphosphate (IP6)], Group 4A-4B (17% EDTA+8 mg/mL propolis), Group 5A-5B (10% CA+8 mg/mL propolis), Group 6A-6B (1% IP6+8mg/mL propolis), Group 7A-7B (8 mg/mL propolis), Control A-B (Dimethyl Sulfoxide). Each tooth was randomly irrigated with 2 mL of one of the group solutions or dispersions for 5 min, and the solutions were examined for the bactericidal effect. Results: For C. albicans, all groups showed less optical density (OD) than the control group (P<0.05). The propolis group and the IP6 group had higher OD values ​​than the CA group (P<0.05). For E. faecalis, on the other hand, significantly lower OD values were observed in the propolis+ CA group, compared to the CA and propolis groups (P<0.05). There was no significant difference between microbial growth among IP6, EDTA, propolis+ CA, propolis+IP6, and propolis+ EDTA groups (P>0.05). Conclusion: CA and IP6 showed promising results in eliminating E. faecalis, one of the collective organisms responsible for failed root canals.